2018
DOI: 10.1111/lasr.12315
|View full text |Cite
|
Sign up to set email alerts
|

How Litigants in Dutch Courtrooms Come to Trust Judges: The Role of Perceived Procedural Justice, Outcome Favorability, and Other Sociolegal Moderators

Abstract: This paper examines the hypothesis that litigants' perceived procedural justice is positively associated with their trust in judges. We argue that although this association might seem quite robust, it can vary across contexts. In particular, we suggest that the nature and magnitude of the association between procedural justice and trust in judges depends on outcome concerns, and other sociolegal moderators such as outcome importance and prior court experience. We tested our predictions in three different types… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 52 publications
3
36
0
1
Order By: Relevance
“…We find that information outlining the procedural context of the decision affects both trust in judges and mitigates negative affect about a verdict. This finding connects with literature that has shown that experience with a fair decision-making procedure engenders trust in authorities (e.g., Tyler 2006;Grootelaar and Van den Bos 2018). In contrast with suggestions by the extant literature on the information effect (e.g., Indermauer and Hough 2002;Mirrlees-Black 2002;De Keijser et al 2007), this implies that it is not about merely providing more factual details or circumstances of a case that drives the information effect.…”
Section: Discussion Of Findingssupporting
confidence: 83%
See 1 more Smart Citation
“…We find that information outlining the procedural context of the decision affects both trust in judges and mitigates negative affect about a verdict. This finding connects with literature that has shown that experience with a fair decision-making procedure engenders trust in authorities (e.g., Tyler 2006;Grootelaar and Van den Bos 2018). In contrast with suggestions by the extant literature on the information effect (e.g., Indermauer and Hough 2002;Mirrlees-Black 2002;De Keijser et al 2007), this implies that it is not about merely providing more factual details or circumstances of a case that drives the information effect.…”
Section: Discussion Of Findingssupporting
confidence: 83%
“…In legal contexts, procedural justice judgments are strongly associated with acceptance of court-ordered arbitration awards (Lind et al 1993), obedience to laws (Tyler 2006) and outcome satisfaction (Casper et al 1988). Furthermore, the amount of information people have available about their social environment tends to affect their procedural fairness judgments (Van den Bos et al 1997;Van den Bos 1999;Van den Bos and Lind 2002), which, in turn, impacts their trust in societal authorities (Grootelaar and Van den Bos 2018). Building on this literature, we test whether providing procedural cues in an informational treatment has a distinct effect on public attitudes in legal contexts.…”
Section: Specifying the Information Effect By Probing Modest And Morementioning
confidence: 99%
“…Such findings, particularly as they pertain to the role of judicial independence in fostering trust, fit well with a vast observational and experimental literature on specific courts stressing the importance of procedural fairness in general, and impartiality in particular, as sources of support (Lind and Tyler, 1988; Tyler and Huo, 2002; Benesh, 2006; Grootelaar and van denBos, 2018). This seems to occur not only in the context of personal experiences in lower courts but also in evaluations of more remote institutions, such as national governments, parliaments, entire political systems, or high courts (Tyler and Caine, 1981; Tyler and Mitchell, 1994; Kershaw and Alexander, 2003; Erlingsson, Linde, and Öhrvall, 2014).…”
Section: The Correlates Of Trust In the Legal Systemsupporting
confidence: 75%
“…Regardless of any uncontrollable circumstances SRLs faced, most participants felt pressured to present as self-composed individuals in court trials or followed court orders. In contrast Grootelaar and van den Bos's (2018) research concluded that when "litigants who perceive the judge's treatment as fair are more likely to trust judges" (p. 264) this attitude did make a difference in their outcomes. Two of the participants viewed their judges favourably, yet lawyers were seen as untrustworthy, but as stated previously.…”
Section: Theme 4: Participants' Perception Of Judges' Behaviours Toward Themmentioning
confidence: 96%